Effects of Subthalamic and Nigral Stimulation on Gait Kinematics in Parkinson’s Disease - Scholten, Marlieke; Klemt, Johannes; Heilbronn, Melanie; Plewnia, Christian; Bloem, Bastiaan R.; Bunjes, Friedemann; Krüger, Rejko; Gharabaghi, Alireza; Weiss, Daniel (Frontiers in Neurology, 2017)
Conventional subthalamic deep brain stimulation for Parkinson’s disease (PD) presumably modulates the spatial component of gait. However, temporal dysregulation of gait is one of the factors that is tightly associated with freezing of gait (FOG). Temporal locomotor integration may be modulated differentially at distinct levels of the basal ganglia. Owing to its specific descending brainstem projections, stimulation of the substantia nigra pars reticulata (SNr) area might modulate spatial and temporal parameters of gait differentially compared to standard subthalamic nucleus (STN) stimulation. Here, we aimed to characterize the differential effect of STN or SNr stimulation on kinematic gait parameters. We analyzed biomechanical parameters during unconstrained over ground walking in 12 PD patients with subthalamic deep brain stimulation and FOG. Patients performed walking in three therapeutic conditions: i) Off stimulation, ii) STN stimulation (alone), iii) SNr stimulation (alone). SNr stimulation was achieved by stimulating the most caudal contact of the electrode. We recorded gait using three sensors (each containing a tri-axial accelerometer, gyroscope, and magnetometer) attached on both left and right ankle, and to the lumbar spine. STN stimulation improved both the spatial features (stride length, stride length variability) and the temporal parameters of gait. SNr stimulation improved temporal parameters of gait (swing time asymmetry). Correlation analysis suggested that patients with more medial localization of the SNr contact associated with a stronger regularization of gait. These results suggest that SNr stimulation might support temporal regularization of gait integration.